Transparency and Accountability Deficits in Indonesian Orphanage Financial Reporting: Defisit Transparansi dan Akuntabilitas dalam Pelaporan Keuangan Panti Asuhan di Indonesia - Zuhrina Rahayu Nisa; Heri Widodo (Academia Open, 2024)
Non-profit organizations play a critical role in society, yet their financial reporting practices often lack the rigor of for-profit entities. This study examines the financial reporting of the Darul Aitam Orphanage Foundation, focusing on its compliance with ISAK 35 standards and its implementation of transparency and accountability principles. Despite the importance of these principles for trust and efficiency, a knowledge gap exists regarding their application in non-profit orphanages. The research employs a qualitative descriptive method, utilizing primary and secondary data from monthly reports, and collects data through observations, interviews, and documentation. Findings reveal that the Darul Aitam Orphanage Foundation has not adopted ISAK 35 standards and fails to fully implement transparency and accountability in its financial reporting. The financial records are rudimentary, noting only cash inflows and outflows, and lack detailed information needed by external stakeholders. These results underscore the need for improved financial practices in non-profit organizations to enhance accountability and transparency, thereby fostering greater trust and support from stakeholders. Highligt: The Darul Aitam Orphanage Foundation's financial reports do not adhere to ISAK 35 standards. The orphanage's financial practices lack comprehensive transparency and accountability. Enhanced financial reporting practices are necessary for better external analysis and stakeholder trust. Keywoard: Financial Reporting, Non-Profit Organizations, ISAK 35 Compliance, Transparency, Accountability